Bi metal/oxygen-deficient BiO2−x with tetrahedral morphology and high photocatalytic activity. (18th November 2020) - Liang, Mengjun; Zou, Chentao; Wang, Weihua; Yang, Zhiyuan; Shen, Kaixiang; Yang, Yun; Yang, Shuijin
Abstract: Vacancy-rich materials with high photocatalytic activity are of great interest for pollutants removal and play a significant role in green chemistry. Herein, we successfully synthesized Bi/BiO2− x composite through hydrothermal route. In this case, the surface plasmon resonance effect of Bi and oxygen vacancies of BiO2− x collectively increase the removal rate of pollutants. More importantly, the Bi/BiO2− x composites have enhanced activity in the degradation of RhB, MO, BPA and CIP, and the reduction of Cr(VI) and PNA. Besides, an enhanced photocatalytic activity is due to the main reactive species of · O 2 − and h + that is confirmed by trapping experiments and ESR analyses. The electronic structure and visible light harvesting of photocatalysts were measured and also theoretically calculated by using density functional theory and finite difference time domain calculations, DRS, VB x-ray photoelectron spectroscopy and Mott–Schottky plots, which allowed to propose a possible photocatalytic mechanism for the degradation process.